Conceptualizing Digital Readiness, Strategic Foresight, and Strategic Flexibility as Drivers of Digitalization and Performance of Small and Medium Enterprises - Alqam, Hanin S; Razzak, Mohammad; Al-Busaidi, Adil; Al-Riyami, Said (JOIV : International Journal on Informatics Visualization, 2024)
The drivers of digitalization and small and medium enterprises (SMEs) performance have been primarily examined through resource-based theories. Hence, this study presents an alternative perspective based on such organizations' readiness and dynamic capabilities through a conceptual framework. A conceptual framework is developed by drawing upon the digital readiness theory (DRT) along with the dynamic capabilities view (DCV) to propose an integrated framework that posits a set of propositions linking constructs that reflect both digital readiness as well as the dynamic capabilities of an organization as possible drivers of business process digitalization (BPD) and performance. The empirical literature based on the DRT suggests that digital readiness will likely drive BPD and performance. Whereas leveraging the premise of the DCV indicates that the ability to sense opportunities and threats is reflected by strategic foresight. In contrast, the ability to seize and transform is reflected through strategic flexibility. The propositions posit that all three factors influence performance directly and through the mediating effect of BPD. The framework developed in this study may provide clues to practitioners and policymakers related to SME development regarding potential drivers of digitalization and performance. Growing scholarly publications on antecedents of digitalization and the performance of SMEs have focused primarily on resources. The current study offers an alternate perspective by integrating the two theories based on such organizations' readiness and dynamic capabilities.